The Effect of Dobbs V. Jackson Women’S Health Organization on Clinical Diagnosis of Postpartum Depression - Sepulveda-Pizarro, F (Columbia Data Analytics, 2025)
Background: The 2022 US Supreme Court decision in Dobbs v. Jackson Women’s Health Organization eliminated the constitutional right to abortion and activated trigger laws in 21 states, either banning or significantly restricting abortion access. This study estimated changes in postpartum depression (PPD) diagnoses after Dobbs in states with trigger laws vs those without. Methods: Medicaid data from Kythera Labs spanning December 2019 to June 2024 were utilized. Difference-in-difference models assessed changes in PPD diagnosis rates post-Dobbs (21 trigger states, 29 non-trigger states). Results: Women in trigger states were younger (mean, 26.53 vs 27.98 years), more likely to reside in low socioeconomic status areas (41.28% vs 24.42%) and less likely to have obstetrical complications (66.06% vs 77.36%), maternal complications (16.41% vs 18.9%), and lifestyle risk factors (13.58% vs 21.17%). Baseline PPD diagnosis rates were 8.51% in trigger states and 12.66% in non-trigger states. Post-Dobbs, PPD diagnosis rates were 10.20% in trigger states and 14.34% in non-trigger states. Conclusions: Overall, women in states with abortion trigger laws experienced a small positive but statistically insignificant increase in PPD diagnoses following Dobbs compared with those in non-trigger states. © 2025 Columbia Data Analytics. All rights reserved.